ChemInform Abstract: Efficient Enantioselective Synthesis of Dihydropyrans Using a Chiral N, N′‐Dioxide as Organocatalyst. Issue 40 (12th September 2013) - Feng, Juhua; Fu, Xuan; Chen, Zhenling; Lin, Lili; Liu, Xiaohua; Feng, Xiaoming
Abstract A (S)‐proline‐derived chiral N‐oxide catalyst is successfully applied to an asymmetric cascade Michael/hemiacetalization reaction yielding multifunctionalized chiral dihydropyrans.